The use of ICT tools in gaining knowledge about law in judicial decisions - Chomiak-Orsa, Iwona; Greńczuk, Andrzej (Wykorzystanie narzędzi ICT w odkrywaniu wiedzy o prawie w orzeczeniach sądowych, 2020)
The use of modern ICT solutions of business intelligence is becoming more and more common, and are also increasingly used in the field of legal regulations, and above all in legal information management, advanced ICT solutions. The purpose of this article is to indicate the possibility of implementing modern ICT tools in order to obtain the knowledge contained in the judicial decisions. Court decisions, as one of the areas of creating and applying law, are a source of information resources for numerous groups of stakeholders. Therefore, the creation and use of IT tools to support the processes of gaining knowledge about law from court decisions is a legitimate direction in the development of legal informatics. The article is the result of literature research dedicated to the applications of ICT solutions in the area of creating and distributing legal information
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 4 (58), s. 80-92
Keywords: informatyka ekonomiczna